2023
DOI: 10.3390/antibiotics12040681
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status and Future Perspectives of Beta-Lactam Therapeutic Drug Monitoring in Critically Ill Patients

Abstract: Beta-lactams (BL) are the first line agents for the antibiotic management of critically ill patients with sepsis or septic shock. BL are hydrophilic antibiotics particularly subject to unpredictable concentrations in the context of critical illness because of pharmacokinetic (PK) and pharmacodynamics (PD) alterations. Thus, during the last decade, the literature focusing on the interest of BL therapeutic drug monitoring (TDM) in the intensive care unit (ICU) setting has been exponential. Moreover, recent guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 86 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Unfortunately, in this particular case, we did not achieve microbiological isolation, which precluded us from conducting a precise assessment of the T/MIC. Nevertheless, when considering one of the worst-case scenarios, 16 mg/L, corresponding to the ECOFF of Pseudomonas aeruginosa, according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST), as a surrogate MIC value [22,23], we observed that, in the initial measurement, piperacillin blood concentrations exceeded the presumed MIC for the suspected bacterium but fell slightly below the PD target of four times the MIC (64 mg/L) specified for beta-lactams [24,25]. However, 7 days and 10 days from the initiation of antibiotic treatment, piperacillin blood concentrations were substantially superior to the PD target, by four times compared to the MIC.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in this particular case, we did not achieve microbiological isolation, which precluded us from conducting a precise assessment of the T/MIC. Nevertheless, when considering one of the worst-case scenarios, 16 mg/L, corresponding to the ECOFF of Pseudomonas aeruginosa, according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST), as a surrogate MIC value [22,23], we observed that, in the initial measurement, piperacillin blood concentrations exceeded the presumed MIC for the suspected bacterium but fell slightly below the PD target of four times the MIC (64 mg/L) specified for beta-lactams [24,25]. However, 7 days and 10 days from the initiation of antibiotic treatment, piperacillin blood concentrations were substantially superior to the PD target, by four times compared to the MIC.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our study revealed overestimation and mediocre performance of the respective model in the investigated critically ill patients (A/B1/B2: MPE 24.9/18.6/22.8%; MAPE 43.5/34.6/36.9%). Thus, it can only be speculated whether model selection had a relevant influence on the study results, also because the trial included several β-lactams, whereas our study included only PIP [ 22 , 47 , 48 ]. However, both studies combined highlight the key role of externally evaluating PopPK models prior to clinical implementation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the unbound fraction may vary in critically ill patients, and possible skewing of the results can therefore not be excluded [ 27 , 32 , 51 ]. Sixth, our study exemplarily followed a recommended PIP c target of 64 mg/L, but for β-lactams “the optimal PK/PD target remains debated” according to Novy et al [ 47 ]. A range of 32–96 mg/L was considered acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the difficulty in accurately dosing antibiotics, therapeutic drug monitoring (TDM) has become the standard of care for many antibiotics, including vancomycin, aminoglycosides, and linezolid and increasingly being considered for beta lactam antibiotics [2]. With this approach, knowledge of a drug's plasma concentration is used to inform future drug dosing.…”
Section: Therapeutic Drug Monitoring In the Critically Ill Is Challen...mentioning
confidence: 99%